“Aplicultura y producción de miel de abejas (apis mellifera L.) en las zonas del huallaga central y bajo mayo – región San Martín” - Pareja Ugarte, Guido Renato (2007)
The region of San Martín by important variability micro climate which in turn has a very high honey biological richness, is contributing to the socio-economic and ecological development of the region. Some thousands of years before Christ, he is known and talks about honey. Writers, philosophers, theologians and scientists in general, among others, have devoted efforts and part of his time to studying their qualities and use, having left a wealth of knowledge on the subject, however at present, the conditions of our regional beekeeping, still ignores the advantages nutritional, commercial and medicinal honey. Thanks to this advantage, the demand for the product in the Lima market and the support of institutions with the help of international cooperation, beekeeping in the region is taking a technological and commercial momentum. Individual beekeepers as organized, despite their technological limitations and climatic risks...